Iridoids and bis-iridoids from Valeriana jatamansi and their cytotoxicity against human glioma stem cells. (July 2020) - Quan, Li-Qiu; Hegazy, Ahmed-Mohamed; Zhang, Zhi-Jun; Zhao, Xu-Dong; Li, Hong-Mei; Li, Rong-Tao
Abstract: An undescribed iridoid (valeridoid A) and five undescribed bis-iridoids (valeridoids B–F), along with four known ones, were isolated from the roots and rhizomes of Valeriana jatamansi . Their structures were elucidated based on 1D and 2D NMR, as well as HRESIMS spectroscopic data. In addition, 8, 9-didehydro-7-hydroxydolichodial and valeridoid F were found to inhibit the growth of three human glioma stem cells (GSC-3#, GSC-12# and GSC-18#). Graphical abstract: Image 1 Highlights: Six undescribed iridoid and bis-iridoids were isolated from Valeriana jatamansi. This was the first report of bis-iridoids isolated from Valeriana jatamansi. Two compounds could inhibit the growth of human glioma stem cells.